IMPROVING STUDENTS’ VOCABULARY LEARNING THROUGH EXTENSIVE READING (A STUDY OF STUDENTS IN MUHAMMADIYAH UNIVERSITY OF MAKASSAR) - ariana ariana (UIN Alauddin Makassar, 2018)
This research aims at finding out whether or not using of extensive reading was effective to develop the English vocabulary of the fifth semester students of Muhammadiyah University of Makassar. It was quasi experimental research design. This research took place at Muhammadiyah University of Makassar in academic year 20105/2016. The population of the research was 313 students. The sample of this research consisted of 52 students, 28 students as the control group and 24 students as the experimental group, which was chosen by using cluster random sampling technique. The instrument of collecting data was vocabulary test. The data were obtained through pretest and posttest for both groups and the result of the test was analyzed by using SPSS 17.0 version. The result of the data analysis showed that the application of extensive reading was effective to develop the English vocabulary of the fifth semester students of Muhammadiyah University of Makassar proved by the mean score of control group in pretest was 29.31 and the mean score of experimental group was 41.64. While the mean score of control group in posttest was 47.07 which was taught intensive reading and the mean score of experimental group was 59.86, which was taught extensive reading. It means that the improvement of vocabulary achievement in control group from pretest to posttest was 17.76 and in experimental group were 18.22. It means that Incidental vocabulary occurred both of Intensive Reading and Extensive Reading, but the improvement of incidental vocabulary learning in extensive reading was greater than that of intensive reading (18.22>17.76).